Kontribusi Ketekunan Shalat 5 Waktu Dan Rutinitas Membaca Al-Qur'an Terhadap Kedisiplinan Siswa Kelas Atas Sd Muhammadiyah Program Khusus Nogosari - Baikuni, Muhammad Khabib; , Drs. H. Mulyadi Sri Kamulyan, S.H, M.Pd (2017)
This research aims to (1) determine the contribution of perseverance to pray five times towards discipline on the upper grade students in the Muhammadiyah Primary School of Nogosari (Special Program). (2) determine the contribution of reading the Qur'an routine towards discipline on the upper grade students in the Muhammadiyah Primary School of Nogosari (Special Program). (3) determine the contribution of perseverance to pray 5 times and routine reading the Qur'an routine towards discipline on the upper grade students in the Muhammadiyah Primary School of Nogosari (Special Program). This research is quantitative research, the population in this research is upper grade namely IV, V and VI in the Muhammadiyah Primary School of Nogosari (Special Program). The sample of this research is 50 students by using Proportionate Stratified Random Sampling technique. Data collection techniques is questionnaires, documentation and observation. The analysis technique is multiple regression analysis that precedes the prerequisite test analysis. The results of the research show that: 1) There is contribution from perseverance of praying five times towards discipline on the upper grade students in the Muhammadiyah Primary School of Nogosari (Special Program). Based on T test is obtained: Tcount ˃ Ttable (3,176 ˃ 2.011) and significant value ˂ 0.05 (0003 ˂ 0.05). 2) there is a contribution from routine of reading the Qur'an towards discipline on the upper grade students in the Muhammadiyah Primary School of Nogosari (Special Program). Based on T test is obtained: Tcount ˃ Ttable (3,239 ˃ 2.011) and significant value ˂ 0.05 (0002 ˂ 0.05). 3) there is contribution from of reading the Qur'an routine towards discipline on the upper grade students in the Muhammadiyah Primary School of Nogosari (Special Program). Based on F test is obtained: Fcount ˃ Ftabel (65 841 ˃ 3.20) and ˂ significance value of 0.05 (0.000 ˂ 0.05). The results of determination test (R2) is 0.737 mean that is from this coefficient is that the contribution is given by a variable combination of perseverance to pray 5 times and routine of reading the Qur'an with discipline on the upper grade students in the Muhammadiyah Primary School of Nogosari (Special Program) is 73.7% while the remnant is 26.3% influenced by other variables. Keywords: praying five times, reading Qur'an, discipline students.